1951
DOI: 10.1039/an9517600696
|View full text |Cite
|
Sign up to set email alerts
|

The assay of vitamin B12. Part VI. Microbiological estimation with a mutant of Escherichia coli by the plate method

Abstract: A method for the microbiological cup-plate assay of vitamin B,, with a mutant of Escherichia coli as test organism is presented. The assay is an advance on other methods previously published as Parts I11 and I V of this series because (a) a simple chemically defined medium is used, (b) changes in the EH of the test medium have little effect on the response, (c) the zones of exhibition are reproducible and well defined in character and ( d ) the degree of specificity and general freedom from interfering effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1952
1952
1999
1999

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…It has been shown by Harrison et al (1951) and confirmed by us that there is a straight line relationship between the diameter of the rings of exhibition and the logarithm of the dose of pure vitamin B12, between the concentrations 0-005 fig./m\. and 0-2 ^g./ml.…”
Section: Dose Response Relationshipmentioning
confidence: 70%
“…It has been shown by Harrison et al (1951) and confirmed by us that there is a straight line relationship between the diameter of the rings of exhibition and the logarithm of the dose of pure vitamin B12, between the concentrations 0-005 fig./m\. and 0-2 ^g./ml.…”
Section: Dose Response Relationshipmentioning
confidence: 70%
“…of vitamin B12/ml. assessed by microbiological assay with an Escherichia coli mutant (Harrison, Lees & Wood, 1951).…”
Section: Methodsmentioning
confidence: 99%
“…needle tips (Harrison et al 1951) which the operator strokes over the surface of the incubated assay plate to align the needle tips and the zone edge by means of a diffuse transverse light source. needle tips (Harrison et al 1951) which the operator strokes over the surface of the incubated assay plate to align the needle tips and the zone edge by means of a diffuse transverse light source.…”
Section: Destcn Of Large Plate Assaysmentioning
confidence: 99%
“…In these large plate methods we measure the zones with calipers having 1 in. needle tips (Harrison et al 1951) which the operator strokes over the surface of the incubated assay plate to align the needle tips and the zone edge by means of a diffuse transverse light source. Since the operator cannot see the alignment of the needle tips and the caliper vernier reading a t one and the same time, two completely independent operations are involved and this method of reading, though a little tedious, is regarded as more objective than others tried.…”
Section: Destcn Of Large Plate Assaysmentioning
confidence: 99%